The Urgency of Establishing Legal Instruments Against Potential Artificial Intelligence (AI) Crimes - Perkasa, Anggada; Siregar, Andini Pratiwi; Keliat, Venia Utami (Ilmu Hukum Prima (IHP), 2025)
The development of artificial intelligence (AI) has brought significant progress in various sectors, but on the other hand, it also presents the potential for crimes that have not been fully accommodated in the existing legal system. Crimes involving AI such as deepfakes, data manipulation, autonomous cyber attacks, and misuse of algorithms raise serious issues in terms of legal accountability, perpetrator identification, and victim protection. The criminal law system in Indonesia, which generally still relies on the principles of legality and the subjectivity of human error, does not yet have adequate legal instruments to address AI-based crimes that are autonomous and adaptive. This study aims to examine the legal vacuum that occurs, evaluate regulations in several other countries as a comparison, and offer the urgency and direction of the formation of new legal instruments in Indonesia. The method used is juridical-normative with a comparative and conceptual approach. The results of the study indicate the need to establish a special legal framework regarding AI, both in the form of new laws and reformulation of criminal norms that can accommodate the unique nature of artificial intelligence. Without adaptive legal reform, Indonesia will face serious legal loopholes that can be exploited by digital criminals.